Solid state chemistry - Smart, Lesley E.; Moore, Elaine A. ([S.l.] : CRC Press, 1995)
Intended for first- and second-year undergraduates, this introduction to solid-state chemistry includes practical examples of applications and modern developments to offer students the opportunity to apply their knowledge in real-life situations. It aims to provide students with a thorough understanding of the traditional knowledge of crystal structures: lattices, unit cells, close packing, and octahedral and tetrahedral holes and their occupation by various ions in the well-known crystal structures. This descriptive work is augmented by free-electron and band theory. Links to other branches of chemistry and practical examples are emphasized, as are the links back to band theory and crystal structures. For this second edition, the book has been updated throughout and has two new chapters, one on X-ray diffraction techniques and another on solid-state preparative methods, as well as new sections on symmetry and ferroelectrics.
Keywords: chemistry,solid estste chemistry